Implementasi Hak Imunitas DPR Ditinjau Berdasarkan Undang-Undang Nomor 17 Tahun 2014 Tentang MPR, DPR, DPD dan DPRD - Raphael, Axel (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2025)
No one has the authority to revoke the right to total immunity. Although the right to qualified immunity is relative, it can still be denied if it is used